The Lord is my shepard: confronting religion in the mass effect trilogy - Irizarry, Joshua A. (Online - Heidelberg journal of religions on the internet, 2014)
Many science-fiction universes present a “perfected” secular future where technological advances have replaced religion. In this context, characters ascribing to religious beliefs are seen as close-minded and flawed. While the same may be said of the Mass Effect video game universe, in this paper we argue that “religion” is actually an abstract character that is always present and active, largely introduced through non-player characters and the structure of the gameplay. Through these narrative devices, the player is subtly immersed in a religious conversation that they are likely not even aware is taking place, guiding them and shaping their perspectives on religion. However, in the trilogy’s controversial ending, players were vocally dissatisfied by the choice they were forced to make, and ultimately, the developers felt compelled to release a new ending for the game. What was it about the original ending that players found so distasteful? We argue that in the Mass Effect universe where religion is shown to be culturally and politically divisive and frequently racist, players were jarred that the final “confrontation” required them to make an overtly religious choice. Players were so emotionally affected that they took to the Internet to debate the ending, define themselves by the choice they made, and demand from the developers the ending they “imagined” they deserved. We will show how the Mass Effect trilogy, ostensibly a story about the struggle against religious hegemony, ultimately compels the player to confront their own beliefs about religion, and consequently about the nature of religious belief.